Enhancing employability: Merdeka campus policy and facilities mediated by industrial collaboration - Alexander Batara Marpaung; John Tampil Purba; Martinus Tukiran (Jurnal Mantik, 2026)
This study examines how the effectiveness of the Merdeka Campus policy and the quality of university service facilities contribute to student employability, with industrial collaboration positioned as a mediating mechanism. Drawing on the Resource-Based View (RBV), the research conceptualizes institutional policies and facilities as strategic resources that can generate competitive advantages for graduates when effectively aligned with external partnerships. A quantitative design was adopted, using purposive sampling to collect data from 311 final-year students and recent graduates in the Greater Jakarta area. The data were analyzed through Covariance-Based Structural Equation Modeling (CB-SEM). The results indicate that both the effective implementation of the Merdeka Campus policy and the adequacy of service facilities significantly strengthen industrial collaboration. In turn, industrial collaboration plays a pivotal mediating role, substantially enhancing the positive effect of university resources on student employability. These findings suggest that institutional resources alone are insufficient; their impact is maximized when integrated with meaningful industry engagement. The study therefore underscores the importance for higher education institutions to align flexible academic policies and supportive infrastructure with sustained industry partnerships in order to better address labor market demands and narrow the gap between graduate competencies and employer expectations.